- #1

- 501

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter DB
- Start date

- #1

- 501

- 0

- #2

AKG

Science Advisor

Homework Helper

- 2,565

- 4

The derivative of cos(x) as x->0 is -sin(x) as x->0 is -sin(0) is 0, not 1. But simply cos(x) as x->0 is cos(0) = 1. the derivative of cos(3x) as x->0 = -3sin(3x) as x->0 = -3sin(3*0) = -3sin(0) = -3*0 = 0. cos(3x) as x->0 = cos(3*0) = cos(0) = 1. The derivative of cos(x) as x->a = -sin(x) as x->a = -sin(a). The derivative of cos(3x) as x->a = -3sin(3x) as x->a = -3sin(3a).

Last edited:

- #3

mathman

Science Advisor

- 8,005

- 518

The derivative of cos(x) is -sin(x).

- #4

AKG

Science Advisor

Homework Helper

- 2,565

- 4

Yeah, I knew that. Edited.

- #5

- 505

- 0

- #6

HallsofIvy

Science Advisor

Homework Helper

- 41,847

- 966

DB said:

The derivative of

- #7

- 21

- 0

- #8

HallsofIvy

Science Advisor

Homework Helper

- 41,847

- 966

The derivative of a function of x is a function of x and can approach a limit as well as any function.cDimino said:

- #9

- 505

- 0

This is how the chain rule can be derived....

- #10

- 218

- 0

just U-substitute u=3x if you must and apply chain rule. dy/dx=dy/du*du/dx

Share: